Pathogenicity of Pythium aphanidermatum and P. oopapillum in hydroponic lettuce and spinach - Gutierrez Y., Daniela (Zamorano: Escuela Agrícola Panamericana, 2020, 2020)
Pythium species are pathogens that cause root rot in hydroponic crops. The objectives of this study were to determine the optimal growth temperature of P. aphanidermatum and P. oopapillum, their pathogenicity in spinach and lettuce, and a suitable method for spinach inoculation. The mycelial growth rate of P. aphanidermatum, P. oopapillum 06 and P. oopapillum 07 was determined at 15-20-25-30-35 and 40 °C measuring radial growth every 12 hours for 48 hours. Pathogenicity of these isolates was evaluated in a simulated deep-water culture hydroponic system. Lettuce and spinach inoculations were performed using mycelial infected agar discs and a concentration of 10 zoospores mL-1 was evaluated for spinach. Data collected, at 14 days for lettuce and 16 days for spinach, were root length, fresh and dry root weight, and fresh leaf weight. For spinach, root rot severity was also measured. P. aphanidermatum had the highest growth rate at 25-30 °C and P. oopapillum isolates at 30-35 °C. Inoculated lettuces showed a decrease in all measured variables compared to control. Inoculated spinach had lower fresh leaf, root weight and greater root rot severity than controls. P. aphanidermatum presented the greatest decrease in root length, fresh weight of root and leaves and the highest root rot severity (97.5%) when inoculated with zoospores. Inoculation method with the greatest effect in root length, weight and leaf weight were zoospores. P. aphanidermatum and P. oopapillum affected root development resulting in less plant growth. The use of zoospores is a suitable method of inoculation.